La reestructuración industrial y sus efectos en el territorio - Silva Arciniega, Rosa (Pontificia Universidad Católica del Perú. Fondo Editorial, 2005)
This topic is immersed within the study program of the current Plan of Studies «D»for the License in Geography and Territorial Management, Unit 11, New Production and Spatial lmpact's Models. The objective of this program is:to make a detailed analysis of the new industrial facts, especially in relation to the organization foundations and strategic management of industry. lt strengths changes in the re-adaptation processes followed by industry in the developed countries as well as in the Third World. On this basis, it tries to valuate the spatial impacts of thestrategies and new industrial models. (UAEM s/f: 56)Then, the objective of this paper is to show how current world industrial restructuring is leading to deep changes in the territorial organization' patterns. It stresses the modernization of industrial equipment, giving insights about their territorial implications that are leading to industrial restructuring, such as is the case of the maquilas in Mexico.

El tema que se presenta  se ubica  dentro del programa  de Geografía  Industrial,  delactual plan de estudios D de la licenciatura en Geografía y Ordenación del Territorio, unidad 11 («Nuevos modelos de producción e impacto espacial»), cuyo objetivo es:Analizar detalladamente la nueva realidad industrial, en especial todo lo referente a los fundamentos organizativos y a las directrices estratégicas de comportamientos de la industria. Se hace hincapié en los cambios y en los procesos de readaptación seguidos en la industria de los países desarrollados así como en los países del tercer mundo. Sobre esta base, se trata de valorar con profundidad el impacto espacial de las estrate gias y nuevos modelos de industrialización. (UAEM s/f: 56)El objetivo del presente ensayo es mostrar cómo la actual reestructuración indus trial, que se da en el ámbito mundial, desencadena profundas modificaciones en los patrones de organización territorial. Se incide en la modernización de los aparatos industriales y se reflexiona acerca de las implicaciones  territoriales que impulsa la reestructuración industrial, en especial, en el caso de las maquilas de México.
Keywords: Geography; New Development Model; Industrial Restructuring; Territorial Implicancies; Maquilas; Nuevo Modelo de Desarrollo; Reestructuración Industrial; Implicaciones Territoriales; Maquiladoras; https://purl.org/pe-repo/ocde/ford#5.07.00